Boti: Stigma Terhadap Laki-laki Feminin di Lingkungan Kampus - Salsabila, Nuzulul Shofa'; Idrus, Nurul Ilmi (Emik, 2025)
The phenomenon of feminine men who do not conform to hegemonic masculinity norms is often subject to social stigma, particularly through negative labelling, such as the term boti. This study aims to explore the responses of feminine men to such stigma, understand the campus environment’s perception of their identities, examine the construction of gender identity within campus social spaces, and analyze the social impact of stigmatization. This research uses a qualitative approach with a case study method and narrative analysis to explore the experiences of victims of stigma and the social interaction patterns that influence them. Data were collected through interviews with ten informants, consisting of four feminine male students (victims of stigma), two students who perpetrated the stigma, two members of the academic staff (lecturers), and two other students. The findings reveal that feminine men respond to stigma in various ways, including rejecting the label, adapting to the social environment, ignoring the stigma, and accepting it as a form of self-affirmation. The impacts caused by stigma include: labeling and exclusion, social pressure, identity conflict and discomfort in social relations, and the emergence of alternative social dynamics that are exclusive and defensive. The social pressure not only affects their psychological well-being, but also impacts their interpersonal relationships and academic performance. Some experience tension of identity, while others manage to build supportive social spaces. This study emphasizes the importance of creating an inclusive campus environment not merely by promoting tolerance, but by fostering mutual understanding. Through constructive dialogue, campuses can become spaces that promote equality and solidarity for diverse gender expressions